2022
DOI: 10.3390/ijms231810372
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolic Disease in COVID-19, Pathophysiology, Therapy and Prophylaxis

Abstract: For over two years, the world has been facing the epidemiological and health challenge of the coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Growing problems are also complications after the development of COVID-19 in the form of post and long- COVID syndromes, posing a challenge for the medical community, both for clinicians and the scientific world. SARS-CoV-2 infection is associated with an increased risk of cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Whereas the dispensation of vitamin K antagonists and antiplatelet agents did not further increase in the post-COVID period after the first semester, the opposite was true for heparins (B01AB) and particularly for direct oral anticoagulants (B01AF). It is likely that the prescription and dispensation of these drugs was initially meant to continue antithrombotic agents and particularly anticoagulants to control the risk of venous thromboembolism observed in the acute phase of COVID-19 [ 19 ]. Irrespective of whether or not these drugs were appropriately used at the time of acute infection (in hospital, but not at home) [ 20 , 21 ], there is no evidence nor any recommendation to continue them after recovery from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the dispensation of vitamin K antagonists and antiplatelet agents did not further increase in the post-COVID period after the first semester, the opposite was true for heparins (B01AB) and particularly for direct oral anticoagulants (B01AF). It is likely that the prescription and dispensation of these drugs was initially meant to continue antithrombotic agents and particularly anticoagulants to control the risk of venous thromboembolism observed in the acute phase of COVID-19 [ 19 ]. Irrespective of whether or not these drugs were appropriately used at the time of acute infection (in hospital, but not at home) [ 20 , 21 ], there is no evidence nor any recommendation to continue them after recovery from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on this subject have stated that although coagulation-related complications are observed primarily in the lungs, heart, kidneys, and brain in COVID-19, the frequency of arterial and venous thromboembolic events increases throughout the body. These studies reported that the risk of ICU admission, morbidity, and mortality increased with thromboembolic events [23][24][25]. Cheng NM et al in their review study, in which they evaluated 68 publications, reported that the incidence of thromboembolic events increased in severe cases, pulmonary embolism (PE) and deep venous thrombosis (DVT) were the most common forms, and D-dimer was an independent risk factor for thromboembolic events [26].…”
Section: Plos Onementioning
confidence: 99%
“…Endothelial cell damage following SARS-CoV-2 infection leads to disruption of physiologic anticoagulant function and development of a more procoagulant and pro-thrombotic phenotype [ 62 ]. SARS-CoV-2 destroys the endothelium and leads to cell apoptosis, which causes overexpression of coagulation factors VII, VIII and TF, and release of von Willebrand factor, activating intrinsic and extrinsic coagulation pathways [ 63 ].…”
Section: Covid-19 and Venous Thrombosis: Pathogenetic Mechanismsmentioning
confidence: 99%
“…Diagnosed VTE is treated according to the general guidelines. There is no consensus on the duration of therapy (3–6 or even 12 months) [ 88 ].…”
Section: Venous Thrombosis During Covid-19 In the General Populationmentioning
confidence: 99%